(untitled) (Foro de Educacion, 2021)
For decades, Robert Baden Powell’s traditional game of «The Flag» has been the bearer of nationalising codes and disciplinary norms of masculinity. Through a genealogical and deconstructive interpretation of this game, we present a theorising and open didactic hypothesis (without specifying) for education, which tries to invert the original purpose of the game. The objective is to know the origin of the game of «The Flag», its incorporation into school pedagogy and to analyse its internal and external logic. This allows the possibility of changing the traditional vision of the game and to give it a critical conceptual and didactic twist through a more open proposal. The methodology is based on the bibliographical review of primary sources or old books where the features of the game and its variants are described. Secondary sources allow us to consider the state of the question and hermeneutics from a constructivist and Critical Theory point of view. Finally, and as a conclusion, teachers are invited to reflect on the (im)possibilities to allow a didactic twist to this type of games that are depositaries of elements and disciplinary guardians of tradition, that is, to raise a critical re-contextualisation of the use of this type of games in school physical education.